Hambatan Dan Kegagalan Komunikasi Keluarga Antara Orang Tua dan Anak (Komunikasi Efektif dalam Perspektif Islam dan Psikologi) - Alamsyah, Muhibuddin (An-Nasyr, 2024)
This study aims to uncover the barriers and failures in family communication between parents and children. This research employs a qualitative method with a descriptive approach. Data collection techniques used in this study include interviews through questionnaires, observation, and documentation. The findings show that the communication process between parents and children is crucial in helping children understand themselves, their feelings, thoughts, opinions, and desires. Through effective communication, children can more easily identify their emotions accurately, which in turn helps them recognize similar feelings in others. Over time, the more practiced a child becomes in recognizing emotions, the greater their confidence and sense of control over their own feelings, as it becomes easier to manage something they already understand. The study emphasizes that effective communication is expected to prevent disharmony or communication disruptions in the relationships between parents, children, and other family members. Adolescents, in particular, still require significant attention from their parents; however, they also tend to dislike excessive parental involvement in their personal affairs. One key to successful interpersonal communication between parents and adolescents is the empathy demonstrated by parents.